PENYULUHAN PEMANFAATAN LIMBAH SERBUK KAYU SEBAGAI PENGUAT POLIPROPILENA DI PT. LAKSANA TEKHNIK MAKMUR - Herlin Arina; Erfina Oktariani; Rebecca Christine (Politeknik Negeri Sriwijaya, 2023)
PT Laksana Tekhnik Makmur is one of the companies that produces plastic automotive components, so it is interesting to carry out a direct approach to the company to find out the problems being faced. Production processes that use plastic seeds repeatedly, usually provide poor product quality and need improvement. The use of additives, especially antioxidants, which have been researched by a team from STMI Polytechnic, has shown an improvement in product quality. This community service activity, especially for PT Laksana Tekhnik Makmur, provides solutions to the production team to add antioxidants to the raw materials. If the production team implements according to the results of the discussion, a decrease in NG (no good) products can be obtained by 40%. This will increase the profit of the company itself. Keywords: polypropylene, sawdust, antioxidant